Inhibitory effect of Curcuma comosa on NO production and cytokine expression in LPS-activated microglia - Nattinee Jantaratnotai (2018)
Curcuma comosa is an indigenous plant of Thailand, which has been traditionally and widely used as an anti-inflammatory agent for the treatment of postpartum uterine bleeding and uterine inflammation. However, the scientific investigation on its anti-inflammatory activity has not been reported. In the present study, we investigated the anti-inflammatory effect of the extract from C. comosa on the responses in microglia stimulated with lipopolysaccharide (LPS). Pretreatment of highly aggressively proliferating immortalized (HAPI) cells, a rat microglial cell line, with the hexane extract of C. comosa rhizome at 10- 9to 10- 5g/ml significantly suppressed the levels of NO released from these cells. The attenuation in iNOS protein and mRNA expression was also observed suggesting an interference at transcriptional level. In addition, C. comosa extract inhibited interferon regulatory factor-1 expression which is an essential transcription factor governing the iNOS expression. Moreover, the levels of mRNA expressions of MCP-1 and IL-6 induced by LPS were also prominently decreased in the presence of C. comosa extract. These results suggest that C. comosa extract possesses a strong anti-inflammatory activity and has a potential to be developed as a therapeutic compound for diverse neurological disorders associated with inflammation. © 2005 Elsevier Inc. All rights reserved.